Luminescent microcrystalline glass containing nanocrystals and core-shell structure and preparation method thereof
A core-shell structured luminescent microcrystalline glass with Ba0.625Er0.375F2.375 nanocrystals and BaAl2Si2O8 microcrystals addresses the limitations of traditional fluoride-oxygen microcrystalline glass by enhancing red light emission and stability, suitable for LED lighting.
Patent Information
- Application Number
- CN202411338008.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-25
AI Technical Summary
Existing rare earth luminescent materials, particularly fluoride-oxygen microcrystalline glass, lack a matrix material that effectively integrates luminescence performance with stability and prevents particle agglomeration, limiting their application range.
A core-shell structured luminescent microcrystalline glass is developed, comprising a core layer of Ba0.625Er0.375F2.375 nanocrystals and a shell layer of BaAl2Si2O8 microcrystals, achieved through specific glass composition and heat treatment processes, enhancing luminescence performance and stability.
The core-shell structure enhances red light emission under ultraviolet excitation, offering a simple preparation method and easy molding, suitable for LED lighting applications.
Smart Images

Figure CN118851567B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of rare earth luminescent materials, and in particular to luminescent microcrystalline glass containing nanocrystals and core-shell structures and a preparation method thereof. Background Art
[0002] In order to further expand the application scenarios and luminescent properties of rare earth luminescent materials, it is necessary to find a matrix material with good physical and chemical properties suitable for rare earth ion doping. Fluoride oxy-glass-ceramics is a composite material composed of fluoride nanocrystals and oxide glass. It has the advantages of low phonon energy of fluoride nanocrystals and good physical and chemical properties and easy molding of oxide glass. It is an ideal rare earth ion luminescent matrix material.
[0003] Core-shell structured materials are materials with special structures formed by connecting the core layer material and the shell layer material through physical or chemical action. The unique structural characteristics of rare earth-doped core-shell structured luminescent materials can integrate the properties of the two materials and supplement their respective deficiencies. For example, the core layer material has good luminescence performance, while the shell layer has the functions of maintaining the stability of the core material, preventing internal particle agglomeration and controlling particle interface reactions, which expands the application range of rare earth-doped nanomaterials. Traditional fluoride-oxygen microcrystalline glass is made by regulating the glass composition and heat treatment process to precipitate a single fluoride nanocrystal in the glass matrix, while core-shell structured microcrystalline glass needs further research. Therefore, by designing special glass components and preparation processes, the preparation of fluorescent microcrystalline glass with a core-shell structure is expected to further improve the luminescence performance of rare earth ions and expand the application scenarios of rare earth-doped microcrystalline glass. Summary of the invention
[0004] The object of the present invention is to provide a luminescent microcrystalline glass containing a core-shell structure and a preparation method thereof, so as to solve the problems existing in the above-mentioned prior art.
[0005] To achieve the above object, the present invention provides the following solutions:
[0006] One of the technical solutions of the present invention is to provide a green luminescent glass, wherein the molar percentage of raw materials is as follows:
[0007] SiO240~60mol%, Al2O310-25mol%, Na2O 5-15mol%, ErF31-5mol%, YbF31-5mol% 、BaF215-20mol%;
[0008] The preparation method of the green luminescent glass comprises the following steps:
[0009] The raw materials are mixed and melted, the obtained melt is molded, and then annealed at 450-500° C. to obtain the green luminescent glass.
[0010] The second technical solution of the present invention is to provide a Ba 0.625 Er 0.375 F 2.375 The molar percentage of raw materials of nanocrystalline red luminescent glass-ceramics is as follows:
[0011] SiO240~60mol%, Al2O310-25mol%, Na2O 5-15mol%, ErF31-5mol%, YbF31-5mol% 、BaF215-20mol%;
[0012] The Ba 0.625 Er 0.375 F 2.375 The method for preparing nanocrystalline red luminescent glass-ceramics comprises the following steps:
[0013] The raw materials are mixed and melted, the obtained melt is molded, and then annealed and heat-treated in sequence to obtain the Ba-containing 0.625 Er 0.375 F 2.375 Nanocrystalline red luminescent glass-ceramics;
[0014] The annealing temperature is 450-500°C, and the heat treatment temperature is greater than or equal to 580°C and less than 710°C.
[0015] As a further preferred embodiment of the present invention, preparation of Ba 0.625 Er 0.375 F 2.375 When the nanocrystalline red luminescent glass-ceramics is melted, the melting temperature is 1400-1600°C, the melting time is 45-60 minutes, and the heat treatment time is 2-5 hours. More preferably, the step of heat preservation for 30-60 minutes is further included after melting.
[0016] The third technical solution of the present invention is to provide a Ba 0.625 Er 0.375 F 2.375 @BaAl2Si2O8 core-shell structure red luminescent glass-ceramics, the molar percentage of raw materials is as follows:
[0017] SiO240~60mol%, Al2O310-25mol%, Na2O 5-15mol%, ErF31-5mol%, YbF31-5mol% 、BaF215-20mol%;
[0018] The Ba 0.625 Er 0.375 F2.375 The preparation method of red luminescent glass-ceramics with @BaAl2Si2O8 core-shell structure comprises the following steps:
[0019] The raw materials are mixed and melted, the obtained melt is subjected to molding treatment, and then annealing and heat treatment are performed in sequence to obtain the Ba-containing 0.625 Er 0.375 F 2.375 @BaAl2Si2O8 core-shell structure red luminescent glass-ceramics;
[0020] The annealing temperature is 450-500°C, and the heat treatment temperature is 710-750°C.
[0021] As a further preferred embodiment of the present invention, preparation of Ba 0.625 Er 0.375 F 2.375 @BaAl2Si2O8 core-shell structure of red luminescent glass-ceramics, the melting temperature is 1400-1600°C, the melting time is 45-60 minutes, the heat treatment time is 2-5 hours. More preferably, after melting, the step of heat preservation for 30-60 minutes is also included.
[0022] As a further preferred embodiment of the present invention, the core-shell structure is Ba 0.625 Er 0.375 F 2.375 It is the crystal core and BaAl2Si2O8 is the shell.
[0023] As a further preferred embodiment of the present invention, the Ba 0.625 Er 0.375 F 2.375 It is a nanometer-scale tetragonal phase crystal, and the BaAl2Si2O8 is a micrometer-scale hexagonal phase crystal.
[0024] In the raw material components of the microcrystalline glass of the present invention, Na2O acts as a network exosome in the glass structure and is used to adjust the glass structure, but does not participate in crystallization.
[0025] A fourth technical solution of the present invention is to provide the application of the above green luminescent glass as a luminescent material in the field of lighting.
[0026] The fifth technical solution of the present invention is to provide the above-mentioned Ba 0.625 Er 0.375 F 2.375 Application of nanocrystalline red luminescent glass-ceramics as luminescent material in the field of lighting.
[0027] The sixth technical solution of the present invention is to provide the above-mentioned Ba 0.625 Er 0.375 F 2.375@BaAl2Si2O8 core-shell structured red luminescent glass-ceramics is used as a luminescent material in the field of lighting.
[0028] In the present invention, the rare earth ion Er 3+ It is both a constituent element of nanocrystals and a luminescent center. In the base glass without heat treatment, Er 3+ The luminescent color under ultraviolet light excitation is green; Ba is precipitated through heat treatment at a certain temperature. 0.625 Er 0.375 F 2.375 Nanocrystals, Er 3+ The luminescent color under ultraviolet light excitation changes from green to red; further increasing the heat treatment temperature, Ba 0.625 Er 0.375 F 2.375 Nanocrystals are used as cores to precipitate hexagonal BaAl2Si2O8 microcrystals, forming Ba 0.625 Er 0.375 F 2.375 @BaAl2Si2O8 core-shell structure, Er 3+ The red luminescence is further enhanced.
[0029] The present invention uses fluorine oxysilicate glass as the base glass, and precipitates Ba in the glass through constant temperature heat treatment. 0.625 Er 0.375 F 2.375 Nanocrystal or Ba 0.625 Er 0.375 F 2.375 @BaAl2Si2O8 core-shell structure crystal. Among them, the core-shell structure is based on the tetragonal Ba 0.625 Er 0.375 F 2.375 As the core, hexagonal BaAl2Si2O8 as the shell, tetragonal Ba 0.625 Er 0.375 F 2.375 It evolved from BaF2, 3+ Three eighths of the cation sites are randomly occupied.
[0030] Yb 3+ Ba was incorporated as a sensitizer 0.625 Er 0.375 F 2.375 Nanocrystals, due to their special crystal structure, Yb 3+ and Er 3+ A cross-relaxation process occurs between Er 3+ The red luminescence is greatly enhanced, making the glass-ceramic exhibit red light emission.
[0031] The present invention has Ba 0.625 Er 0.375 F2.375 @BaAl2Si2O8 core-shell structured glass-ceramics has a simple preparation method and emits strong red light under ultraviolet light excitation. It is a new type of red luminescent material.
[0032] The present invention discloses the following technical effects:
[0033] (1) Under the excitation of ultraviolet light, the glass-ceramics provided by the present invention undergoes a special crystal structure and a cross-relaxation process between rare earth ions. 3+ The red light of the glass-ceramic sample is greatly enhanced, so the glass-ceramic sample shows strong red light emission. The glass-ceramic with a core-shell structure prepared by the present invention can be used as a red light luminescent material in the field of LED lighting.
[0034] (2) Ba provided by the present invention 0.625 Er 0.375 F 2.375 @BaAl2Si2O8 core-shell structured glass-ceramics have the advantages of simple preparation method, easy molding and mass production compared with traditional core-shell structured nanocrystals. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0036] Figure 1 XRD diagrams of the base glass prepared in Example 1 of the present invention and the glass-ceramics obtained by different heat treatments.
[0037] Figure 2 These are microscopic magnified images of the surfaces of the microcrystalline glasses obtained by different heat treatments in Example 1 of the present invention; wherein (a) is the microcrystalline glass prepared by heat treatment at 640°C, (b) is the microcrystalline glass prepared by heat treatment at 710°C, and (c) is the microcrystalline glass prepared by heat treatment at 750°C.
[0038] Figure 3 TEM images of glass-ceramics obtained by different heat treatments in Example 1 of the present invention; wherein (a) is the glass-ceramics prepared by heat treatment at 640°C, (b) is the glass-ceramics prepared by heat treatment at 710°C, and (c) is the glass-ceramics prepared by heat treatment at 750°C.
[0039] Figure 4 The emission spectra of the base glass in Example 1 and the microcrystalline glass obtained by different heat treatments under 378 nm ultraviolet light excitation.
[0040] Figure 5 XRD diagram of the glass-ceramic sample prepared in Comparative Example 1;
[0041] Figure 6 The emission spectra of the base glass and glass-ceramic samples prepared in Comparative Example 1 under 378 nm ultraviolet light excitation. DETAILED DESCRIPTION
[0042] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0043] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0044] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0045] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0046] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0047] In the following examples of the present invention, the purity of SiO2 is 99.99%.
[0048] Example 1
[0049] Each raw material component was weighed according to the molar percentage in Table 1, and the total weight of the raw material components was 20 g.
[0050] Table 1
[0051]
[0052] (1) Raw material mixing and melting: Grind each raw material component in a mortar and mix them evenly. Pour the resulting mixture into a corundum crucible and place it in a high-temperature lifting furnace at 1500°C for melting for 45 minutes.
[0053] (2) Molding: The obtained molten glass is quickly poured onto an iron plate at room temperature and pressed into a block of glass with another iron plate;
[0054] (3) Annealing: The obtained bulk glass is placed in a muffle furnace at 500°C for annealing for 2 hours, and then cooled to obtain the base glass;
[0055] (4) Heat treatment: The obtained base glass was placed in a muffle furnace at 640°C, 710°C and 750°C for 2 h to obtain the corresponding microcrystalline glass products.
[0056] The XRD patterns of the base glass prepared in Example 1 and the glass-ceramics obtained by different heat treatments are as follows: Figure 1 shown.
[0057] The base glass is an amorphous structure. After heat treatment at 640℃, Ba is precipitated in the glass. 0.625 Er 0.375 F 2.375 Nanocrystalline; when the heat treatment temperature is increased to 710℃, Ba 0.625 Er 0.375 F 2.375 As the nucleus, BaAl2Si2O8 was precipitated; when the heat treatment temperature was 750℃, the grain size of BaAl2Si2O8 reached micrometer level, which was much larger than that of nanometer BaAl2Si2O8. 0.625 Er 0.375 F 2.375 , resulting in the XRD pattern showing mainly the hexagonal phase BaAl2Si2O8.
[0058] Figure 2 These are microscopic enlarged images of the surfaces of the microcrystalline glasses obtained by different heat treatments in Example 1, wherein (a) is the microcrystalline glass prepared by heat treatment at 640°C, (b) is the microcrystalline glass prepared by heat treatment at 710°C, and (c) is the microcrystalline glass prepared by heat treatment at 750°C.
[0059] like Figure 2 As shown in (a), due to the precipitation of Ba during heat treatment at 640℃ 0.625 Er 0.375 F 2.375 The grain size is nanometer-scale, so no obvious particles can be seen in the microscopic magnified photos of the surface of microcrystalline glass; Figure 2As shown in (b), when heat treated at 710℃, Ba 0.625 Er 0.375 F 2.375 Nanocrystals are used as crystal nuclei to precipitate micron-sized BaAl2Si2O8 crystals; Figure 2 As shown in (c), when the heat treatment temperature reaches 750°C, the crystallinity of BaAl2Si2O8 is further improved, and obvious grain boundaries can be seen in the micrograph of the surface of the microcrystalline glass.
[0060] Figure 3 TEM images of the microcrystalline glass obtained by different heat treatments in Example 1.
[0061] Figure 3 In (a), the TEM image of the glass-ceramics prepared by heat treatment at 640 °C is shown. 0.625 Er 0.375 F 2.375 The lattice fringes of the nanocrystal (101) plane indicate that Ba was successfully precipitated at this temperature. 0.625 Er 0.375 F 2.375 Nanocrystals; (b) TEM image of glass-ceramics prepared by heat treatment at 710 °C, where the Ba 0.625 Er 0.375 F 2.375 The lattice fringes of the (112) crystal plane and the (102) crystal plane of BaAl2Si2O8 indicate that Ba 0.625 Er 0.375 F 2.375 (c) is the TEM image of the glass-ceramics prepared by heat treatment at 740℃, in which only the lattice fringes and grain boundaries corresponding to the (104), (102) and (100) crystal planes of BaAl2Si2O8 are observed, indicating that the crystallinity of BaAl2Si2O8 heat-treated at this temperature is high. The TEM test results are consistent with the results of XRD and surface micrographs of glass-ceramics.
[0062] Figure 4 The emission spectra of the base glass in Example 1 and the microcrystalline glass obtained by different heat treatments under 378 nm ultraviolet light excitation.
[0063] Under ultraviolet light excitation, Er in the base glass 3+ The green light intensity is much higher than the red light intensity, so it appears green. After heat treatment, the red light is greatly enhanced, and as the heat treatment temperature increases, the ratio of red to green light intensity increases further.
[0064] Example 2
[0065] Weigh each raw material component according to the molar percentage in Table 2, and the total weight of the raw material components is 20 g.
[0066] Table 2
[0067]
[0068] (1) Raw material mixing and melting: Grind each raw material component in a mortar and mix them evenly. Pour the resulting mixture into a corundum crucible and place it in a high-temperature lifting furnace at 1450°C to melt for 50 minutes.
[0069] (2) Molding: The obtained molten glass is quickly poured onto an iron plate at room temperature and pressed into a block of glass with another iron plate;
[0070] (3) Annealing: The obtained bulk glass is placed in a muffle furnace at 500°C for annealing for 2 hours, and then cooled to obtain the base glass;
[0071] (4) Heat treatment: The obtained base glass was placed in a muffle furnace for heat treatment at 700°C for 5 hours to obtain a Ba-containing 0.625 Er 0.375 F 2.375 @BaAl2Si2O8 core-shell structured red luminescent glass-ceramics.
[0072] Example 3
[0073] Each raw material component was weighed according to the molar percentage in Table 3, and the total weight of the raw material components was 20 g.
[0074] Table 3
[0075]
[0076] (1) Raw material mixing and melting: Grind each raw material component in a mortar and mix them evenly. Pour the resulting mixture into a corundum crucible and place it in a high-temperature lifting furnace at 1550°C to melt for 60 minutes.
[0077] (2) Molding: The obtained molten glass is quickly poured onto an iron plate at room temperature and pressed into a block of glass with another iron plate;
[0078] (3) Annealing: The obtained bulk glass is placed in a muffle furnace at 500°C for annealing for 2 hours, and then cooled to obtain the base glass;
[0079] (4) Heat treatment: The obtained base glass was placed in a muffle furnace for heat treatment at 720°C for 4 hours to obtain a glass containing Ba. 0.625 Er 0.375 F 2.375 @BaAl2Si2O8 core-shell structured red luminescent glass-ceramics.
[0080] Example 4
[0081] Each raw material component was weighed according to the molar percentage in Table 4, and the total weight of the raw material components was 20 g.
[0082] Table 4
[0083]
[0084] (1) Raw material mixing and melting: Grind each raw material component in a mortar and mix them evenly. Pour the resulting mixture into a corundum crucible and place it in a high-temperature lifting furnace at 1480°C to melt for 45 minutes.
[0085] (2) Molding: The obtained molten glass is quickly poured onto an iron plate at room temperature and pressed into a block of glass with another iron plate;
[0086] (3) Annealing: The obtained bulk glass is placed in a muffle furnace at 500°C for annealing for 2 hours, and then cooled to obtain the base glass;
[0087] (4) Heat treatment: The obtained base glass was placed in a muffle furnace for heat treatment at 750°C for 3 hours to obtain a glass containing Ba 0.625 Er 0.375 F 2.375 @BaAl2Si2O8 core-shell structured red luminescent glass-ceramics.
[0088] Comparative Example 1
[0089] Each raw material component was weighed according to the molar percentage in Table 5, and the total weight of the raw material components was 20 g.
[0090] Table 5
[0091]
[0092] (1) Raw material mixing and melting: Grind each raw material component in a mortar and mix them evenly. Pour the resulting mixture into a corundum crucible and place it in a high-temperature lifting furnace at 1470°C to melt for 45 minutes.
[0093] (2) Molding: The obtained molten glass is quickly poured onto an iron plate at room temperature and pressed into a block of glass with another iron plate;
[0094] (3) Annealing: The obtained bulk glass is placed in a muffle furnace at 500°C for annealing for 2 hours, and then cooled to obtain the base glass;
[0095] (4) Heat treatment: The obtained base glass was placed in a muffle furnace for heat treatment at 640°C for 3 h to obtain a glass containing Ba 0.625 Er 0.375 F 2.37 Nanocrystalline glass-ceramics.
[0096] Figure 5The XRD pattern of the glass-ceramic sample prepared in Comparative Example 1 shows that the 3+ In the case of 0.625 Er 0.375 F 2.375 Nanocrystals can still be successfully precipitated from the glass matrix. Figure 6 The emission spectra of the base glass and microcrystalline glass samples prepared in Comparative Example 1 under 378 nm ultraviolet light excitation are shown. 0.625 Er 0.375 F 2.375 Nanocrystals, due to the absence of Yb 3+ , there is no Yb 3+ and Er 3+ The cross relaxation results in the spectral red-green ratios of the base glass and glass-ceramic samples being only 0.21 and 0.13, respectively, showing a green luminescence color.
[0097] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A green luminescent glass, characterized in that: The molar percentage of the raw materials is as follows: SiO240~60mol%, Al2O310-25mol%, Na2O 5-15mol%, ErF31-5mol%, YbF31-5mol%, BaF215-20mol%; The preparation method of the green luminescent glass comprises the following steps: The raw materials are mixed and melted, the obtained melt is molded, and then annealed at 450-500° C. to obtain the green luminescent glass.
2. A kind of Ba 0.625 Er 0.375 F 2.375 Nanocrystalline red luminescent glass-ceramics, characterized in that: The molar percentage of the raw materials is as follows: SiO240~60mol%, Al2O310-25mol%, Na2O 5-15mol%, ErF31-5mol%, YbF31-5mol%, BaF215-20mol%; The Ba 0.625 Er 0.375 F 2.375 The method for preparing nanocrystalline red luminescent glass-ceramics comprises the following steps: The raw materials are mixed and melted, the obtained melt is molded, and then annealed and heat-treated in sequence to obtain the Ba-containing 0.625 Er 0.375 F 2.375 Nanocrystalline red luminescent glass-ceramics; The annealing temperature is 450-500°C, and the heat treatment temperature is greater than or equal to 580°C and less than 710°C.
3. The Ba-containing compound according to claim 2 0.625 Er 0.375 F 2.375 Nanocrystalline red luminescent glass-ceramics, characterized in that: The melting temperature is 1400-1600° C.; the heat treatment time is 2-5 hours.
4. A kind of Ba 0.625 Er 0.375 F 2.375 @BaAl2Si2O8 core-shell structure red luminescent microcrystalline glass, characterized by: The molar percentage of the raw materials is as follows: SiO240~60mol%, Al2O310-25mol%, Na2O 5-15mol%, ErF31-5mol%, YbF31-5mol%, BaF215-20mol%; The Ba 0.625 Er 0.375 F 2.375 The preparation method of red luminescent glass-ceramics with @BaAl2Si2O8 core-shell structure comprises the following steps: The raw materials are mixed and melted, the obtained melt is molded, and then annealed and heat-treated in sequence to obtain the Ba-containing 0.625 Er 0.375 F 2.375 @BaAl2Si2O8 core-shell structure red luminescent glass-ceramics; The annealing temperature is 450-500°C, and the heat treatment temperature is 710-750°C.
5. The Ba-containing compound according to claim 4 0.625 Er 0.375 F 2.375 @BaAl2Si2O8 core-shell structure red luminescent microcrystalline glass, characterized by: The melting temperature is 1400-1600° C.; the heat treatment time is 2-5 hours.
6. The Ba-containing compound according to claim 4 0.625 Er 0.375 F 2.375 @BaAl2Si2O8 core-shell structure red luminescent microcrystalline glass, characterized by: The core-shell structure is composed of Ba 0.625 Er 0.375 F 2.375 It is the crystal core and BaAl2Si2O8 is the shell.
7. The Ba-containing compound according to claim 6. 0.625 Er 0.375 F 2.375 @BaAl2Si2O8 core-shell structure red luminescent microcrystalline glass, characterized by: The Ba 0.625 Er 0.375 F 2.375 It is a nanometer-scale tetragonal phase crystal, and the BaAl2Si2O8 is a micrometer-scale hexagonal phase crystal.
8. Use of the green luminescent glass as claimed in claim 1 as a luminescent material in the field of lighting.
9. The Ba-containing compound according to claim 2 0.625 Er 0.375 F 2.375 Application of nanocrystalline red luminescent glass-ceramics as luminescent material in the field of lighting.
10. The Ba-containing compound according to claim 4 0.625 Er 0.375 F 2.375 @BaAl2Si2O8 core-shell structured red luminescent glass-ceramics is used as a luminescent material in the field of lighting.